THE EFFECT OF ADDING BERBEQUE TO RED SNAPPER (LUTJANUS SP) MEATBALLS ON CONSUMERS' FAVORITES - Kaliky, Nurainy (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
One of the favorite foods of various people is meatballs. Meatballs are processed products made from ground fish meat and seasoned, shaped and then boiled. Meatballs are very easy to process and can be made from various types of fish, both freshwater fish and marine fish. What distinguishes the meatballs from these two fish is the meatball gel that is formed and the delicacy. For this reason, many entrepreneurs of processed fishery products and home industries who make meatballs always pay attention to the elasticity and taste of the meatballs. So that the meatballs produced have a good gel and good taste. To increase people's interest in meatballs, the meatballs are given a barbecue flavor which is very liked by children. This study aims to analyze consumer acceptance of red snapper (Lutjanus sp) barbeque meatballs and is a new source of information for the public regarding the diversification of fishery product processing products. The method used is an experiment with 2 treatments, namely treatment A (barbeque concentration) which is 50 gr (A1), 100 gr (A2), 150 gr (A3) and Treatment B (boiling temperature) 45º C-70ºC for 3 times for 50 minutes. . From the results of the study, it can be seen that the addition of barbecue with a large concentration gives good results on the folding value, texture and smell and color does not show a significant effect